THE IMPACT OF INTELLECTUAL CAPITAL ON THE USE OF CREATIVE ACCOUNTING METHODS - Alaa Mohammed Naif Al-Yasiri (Scholar Express Journals, 2025)
This research aims to ascertain the influence of intellectual capital (human and structural) on creative accounting and its various methodologies employed by economic entities. Clarification of the idea of intellectual capital and its dimensions, along with an explanation of creative accounting and a description of the creative accounting procedures employed by most economic entities. Furthermore, the analysis of the research sample's responses, comprising private banks registered on the Iraqi Stock Exchange, was conducted utilising a questionnaire. Should a substantial consensus emerge regarding the influence of intellectual capital (human and structural) on creative accounting methodologies, coupled with the potential for their enhancement through the engagement of competent, experienced, and academically accomplished individuals, as well as the establishment of a conducive environment for accountants within economic entities, the research sample will facilitate the advanced application of creative accounting techniques to the benefit of the economic unit. The study revealed, utilising statistical techniques, a substantial correlation between intellectual capital and creative accounting among a sample of private Iraqi banks. The research also advocated for economic entities to hire skilled, innovative, and academically qualified personnel in their respective fields, enabling them to comprehend the principles, regulations, and accounting standards effectively to advance the interests of the organisation they serve. Furthermore, personnel are introduced to regular training courses that keep them aware about accounting advancements at both the Arab and international levels, as this is essential for the economic unit's sustained and progressive existence in its domain
Keywords: Intellectual capital; creative accounting; Human Capital